Pengaruh Pondok Modern Assalam Terhadap Perubahan Sosial Keagamaan Masyarakat Sekitarnya - Anisah Indriati (UIN Sunan Kalijaga Yogyakarta, 2011)
The article deals with the effect of Pesantren (Islamic boarding school) to social change, a case study in Assalam boarding school in Temanggung. The interaction and integration of the internal PMA on the one hand, and Gandokan district on the other are proven by the enthusiasm of the people sent their children to PMA’s schooling. Some have come to realize that religious education is very important to child development. Moreover, they believe that sending their children to PMA or other pesantren meant their children could get the same quality of non-religious lesson compared to other type of school.